2015
DOI: 10.3168/jds.2015-9520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nisin on Staphylococcus aureus count and physicochemical properties of Minas Frescal cheese

Abstract: The aim of this work was to evaluate the effects of nisin on in vitro and in situ Staphylococcus aureus counts. For in vitro experiment, milk was inoculated with 5.0 log cfu·mL(-1) of S. aureus and nisin was added at concentrations of 0, 100, 200, 400, and 500 IU mL(-1). The main effect of the bacteriocin was lag phase extension from 0h, for 0 and 100 IU·mL(-1) to 8h, when 200, 400, and 500 IU·mL(-1) of nisin were used; however, log phase was not affected. Microbial growth rate was found to be exponential and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
1
15
0
2
Order By: Relevance
“…Mitra and others () showed that the addition of nisin at a concentration of 1000 AU/mL to both skim milk and whole milk was effective in reducing the initial count of Pseudomonas fluorescens , Enterococcus italicus , Lactobacillus paracasei , Enterococcus mundtii , B. cereus , Enterococcus faecalis , Bacillus thuringiensis , and Acinetobacter spp, to an undetectable level during incubation at 8 °C for 8 to 20 h. In another study, a reduction of 1.2 and 2.0 log cycles in the S. aureus count has been noticed, respectively, after addition of nisin at 100 and 500 IU/mL to Minas traditional Serro cheese (Pinto and others ). Likewise, Felicio and others () reported the effectiveness of nisin in reducing the growth of S. aureus in Minas frescal cheese. Recently, de Oliveira and others () evaluated the antimicrobial potential of nisin against L. monocytogenes , B. cereus , Alicyclobacillus acidoterrestris , and S. aureus in mango, cashew, peach, and soursop juices.…”
Section: Natural Antimicrobial Agents For Food Preservationmentioning
confidence: 94%
“…Mitra and others () showed that the addition of nisin at a concentration of 1000 AU/mL to both skim milk and whole milk was effective in reducing the initial count of Pseudomonas fluorescens , Enterococcus italicus , Lactobacillus paracasei , Enterococcus mundtii , B. cereus , Enterococcus faecalis , Bacillus thuringiensis , and Acinetobacter spp, to an undetectable level during incubation at 8 °C for 8 to 20 h. In another study, a reduction of 1.2 and 2.0 log cycles in the S. aureus count has been noticed, respectively, after addition of nisin at 100 and 500 IU/mL to Minas traditional Serro cheese (Pinto and others ). Likewise, Felicio and others () reported the effectiveness of nisin in reducing the growth of S. aureus in Minas frescal cheese. Recently, de Oliveira and others () evaluated the antimicrobial potential of nisin against L. monocytogenes , B. cereus , Alicyclobacillus acidoterrestris , and S. aureus in mango, cashew, peach, and soursop juices.…”
Section: Natural Antimicrobial Agents For Food Preservationmentioning
confidence: 94%
“…El efecto bactericida o bacteriostático de la nisina y el quitosano solos y en combinación, se determinó sobre dos bacterias multirresistentes seleccionadas. Lo anterior se realizó de acuerdo a Felicio et al (14) y Mirdamani et al (28) con algunas modificaciones. Tubos con caldo Mueller-Hinton conteniendo un inóculo de cada uno de los dos aislados de S. aureus ajustado a la turbidez del tubo 0.5 de la escala de McFarland, se mezclaron asépticamente con la CMI de la nisina, quitosano y del compósito nisina/quitosano.…”
Section: Determinación Del Efecto De La Nisina Quitosano Y Del Compóunclassified
“…El uso de péptidos antimicrobianos (PAMs) como la nisina y polisacáridos biodegradables como el quitosano, representan opciones atractivas (12,13) . La nisina es un péptido de 34 aminoácidos producido por Lactococcus lactis, el cual posee actividad antimicrobiana sobre un amplio rango de bacterias Gram positivas (12) , además de que es considerada como segura por la FAO (14) . Por su parte, el quitosano (poly β- [1][2][3][4]-Nacetyl-D-glucosamina) es un biopolímero lineal producido por la desacetilación química de la quitina, la cual se encuentra en el exoesqueleto de crustáceos e insectos.…”
Section: Introductionunclassified
“…The use of nisin has been suggested to prevent or suppress the growth of Staphylococcus aureus , prolong the shelf life and improve the safety of fresh cheese (Felicio et al . ). Dantas et al .…”
Section: Introductionmentioning
confidence: 97%
“…Fresh cheese can be made with goats' milk or a mixture of goats' and cows' milk to meet consumer demands (Sant'Ana et al 2013). The use of nisin has been suggested to prevent or suppress the growth of Staphylococcus aureus, prolong the shelf life and improve the safety of fresh cheese (Felicio et al 2015). Dantas et al(2016) manufactured probiotic fresh cheese using Lactobacillus casei Zhang as a functional dairy product that presents potential health benefits to provide a differentiated product to consumers.…”
Section: Introductionmentioning
confidence: 99%